Multidimensional Screening With Precise Seller Information - Frick, Mira; Iijima, Ryota; Ishii, Yuhta (Econometrica, 2026)
A multi‐product monopolist faces a buyer who is privately informed about his valuations for the goods. As is well known, optimal mechanisms are in general complicated, while simple mechanisms—such as pure bundling or separate sales—can be far from optimal and do not admit clear‐cut comparisons. We show that this changes if the monopolist has sufficiently precise information about the buyer's valuations: Now, pure bundling always outperforms separate sales; moreover, there is a sense in which pure bundling performs essentially as well as the optimal mechanism. To formalize this, we characterize how fast the corresponding revenues converge to the first‐best revenue as the monopolist's information grows precise: Pure bundling achieves the same convergence rate to the first‐best as optimal mechanisms; in contrast, the convergence rate under separate sales is suboptimal.